Customer service : skills for success / Robert W. Lucas, Principal, Robert W. Lucas Enterprises - Lucas, Robert W.
The eighth edition of Customer Service: Skills for Success focus on different aspects of customer service The Profession, Skills for Success, and Building and Maintaining Relationships. Along with valuable ideas, guidance, and perspectives, readers will also encounter interviews of real-world service providers who offer advice for current and aspiring service professionals